Even Womb Surrogates Think: Rethinking Labour and Maternal Work. Issue 1 (8th November 2019) - Messer, Jane
Feminists are generally agreed that mothering is a form of work, is certainly felt as such and clearly makes economic and social contributions to society, but feminist theory remains unsettled on whether mothering can be theorised through a Marxian understanding of production, reproduction and labour. Stella Sandford revisited the dilemma in this journal, concluding as have others, that the notion of 'maternal labour' was fundamentally dichotomous and that a focus on what is specific to mothering depleted it of its potential character as labour. I argue that the difficulties that have persisted in theorizing mothering as work have arisen from a too-narrow understanding of work and consequently of 'labour'. This paper builds on insights into working, work, maternal work, and capitalism developed by Christophe Dejours, Sarah Ruddick and Nancy Fraser. It argues that with an enriched understanding of work and working being an activity that engages the whole of the subject and which is formative of identity, it is then possible to understand mothering as labour that is both affective, intersubjective and 'reproductive'.